Community Reminder: Participatory contextual reminder environments for local communities. Issue 102 (June 2017) - Sasao, Tomoyo; Konomi, Shin'ichi; Kostakos, Vassilis; Kuribayashi, Keisuke; Goncalves, Jorge
Abstract: Many projects have looked at how communities can co-design shared online repositories, such as Wikimapia and Wikipedia. However, little work has examined how local communities can give advice and support to their members by creating context-aware reminders that may include advice, tips and small requests. We developed the Community Reminder environment, a smartphone-based platform that supports community members to design and use context-aware reminders. We have conducted a one-month field study of Community Reminder to crowdsource and deliver safety-relevant information in a local community. The results show the benefits of involving community members in reminder design and connecting different perspectives. We also show that the proposed approach can broaden participation in local communities. Highlights: We developed platform for designing and using context-aware reminders. The platform was used to crowdsource and deliver information in a local community. We discuss the benefits of supporting different levels of participation.